House of cards : a tale of hubris and wretched excess on Wall Street - Cohan, William D. (New York : Doubleday, 2009)
William D. Cohan's superb and shocking narrative chronicles the fall of Bear Stearns and the end of the Second Gilded Age on Wall Street, explaining how a combination of risky bets, corporate political infighting, lax government regulations and truly bad decision-making wrought havoc on the world financial system.
Includes bibliographical references (p. [451]-456) and index.
Keywords: Bear, Stearns & Co; Investment banking -- United States; Bank failures -- United States; Financial crises -- United States; Wall Street (New York, N.Y.)